CRYPTOSPORIDIUM PARVUM AS RISK FACTOR ON NEONATAL DIARRHEA IN ALPACAS OF CUSCO - Villacorta G., Cecilia (2009)
The objective of the present study was to evaluate the presence of Cryptosporidium parvum as a risk factor to the occurrence of diarrhea in alpacas younger than 15 days of age from peasant communities in the area of Cusco, using a case–control study design. Stool samples were collected from animals with (n=248) and without diarrhea (n=231) during the 2006 calving season. The presence of C. parvum was determined by the Modified Ziehl Neelsen stain technique (MZN). The results were analyzed using a logistic regression model, adjusting potentially confusing variables as age, sex, breed and location of alpacas. The Odds Ratio was 4.3 (C.I. = 2.3–7.9). The study demonstrated that neonatal alpaca positives to C. parvum have 4.3 times higher predisposition to suffer diarrheas in relation to the animals negative to MZN. In addition, significant association was observed between the animals MZN positive and the presence of diarrhea (23.4%; n=58) in comparison with the healthy group (8.6 %; n=20).